The impact of the degree of intimate mixing on the compaction properties of materials produced by crystallo-co-spray drying - Tajber, Lidia (My University, 2020)
Direct compression remains one of the most favourable methods available to produce tablet compacts due to its simplicity, efficiency and cost effectiveness however, the technique still remains unsuitable for the majority of formulations due to materials exhibiting poor physical properties such as inadequate compressibility and deformation mechanisms. Whereas crystallo-co-spray drying of various blends has shown to improve the tabletting properties of poorly processable materials, the role of the solvent feed composition in altering the soluble fraction ratio of the excipient to the drug in a crystallo-co-spray dried agglomerate is not well understood. The aim of this work was to investigate the role of the soluble fraction of a drug (paracetamol) and an excipient (α-lactose monohydrate) on the tabletting properties of their crystallo-co-spray dried agglomerates produced via co-spray drying using various inlet feed solvent compositions in order to vary the soluble fraction of the excipient in the feed. It was found that an increase in excipient soluble fraction in the inlet feed resulted in a greater degree of intimate mixing in the final spray dried powder blend, which in turn led to an improvement in tabletting properties of the poorly processable drug.
PUBLISHED
Keywords: Paracetamol; Lactose; Crystallo-co-spray drying; Compressibility; Compactibility; Properties of tablets; Immunology, Inflammation & Infection; Nanoscience & Materials; PARACETAMOL; SPRAY DRYING; TABLETS